Development of a PCR probe test for identifying Pseudomonas aeruginosa and Pseudomonas (Burkholderia) cepacia. - O'Callaghan, E M (1994)
AIMS--To develop a system of species specific polymerase chain reaction (PCR) and DNA hybridisation based on 16s ribosomal RNA sequences for the identification of Pseudomonas aeruginosa and Pseudomonas (Burkholderia) cepacia in sputum from children with cystic fibrosis. METHODS--Most of the 16s rRNA sequences from strains of Ps aeruginosa, Ps (Burkholderia) cepacia, and Ps putida were determined. PCR primers and DNA probes were synthesised from suitable sequences and then evaluated on bacterial cultures and sputum samples. RESULTS--About 1000 bases of sequence was obtained from strains of Ps aeruginosa, Ps (Burkholderia) cepacia, and Ps putida. PCR of bacterial cultures was species specific, but PCR on sputum resulted in some non-specific amplification products. The subsequent hybridisation reaction was species specific. CONCLUSION--A species specific system of PCR and DNA hybridisation based on 16s rRNA sequences is applicable in clinical practice, and may aid the early diagnosis of respiratory tract infection with small numbers of Ps aeruginosa and Ps (Burkholderia) cepacia in patients with cystic fibrosis.